Book Reviews (Historia, 2021)
1. R. Floud: An Introduction to Quantitative Methods for Historians2. J. A. Faber: Drie eeuwen Friesland3. E. M. W. Tillyard: The Elizabethan World Picture4. C. H. Price: George Rex, King or Esquire?5. B. B. Cohen: Writing about Literature6. B. Kearney: Architecture in Natal from 1824 tot 18937. M. C. Kitshoff: Gottlieb Wilhelm Antony van der Lingen8. E. C. Tabler: Pioneers of South West Africa and Ngamiland9. H. Levin: The Myth of the Golden Age in the Renaissance10. Van Stamverwante Bodem deur dr. J. Ploeger